Tuning Convolution Neural networks for Hand Written Digit Recognition - Pondhu, Laxmi Narayana; Pondhu, Govardhani (International Journal of Computer Sciences and Engineering, 2025)
Complex neural networks will take much time for training; we can achieve better accuracy with simpler models by tuning hyper-parameters of the model. Hyper parameter tuning is required for neural networks to improve the accuracy and to reduce the training time of neural networks. In this paper we used simple CNN model with four convolution layers, two pooling layers and two fully connected layers with hyper parameter tuning, batch normalization, learning rate decay, and normalization techniques to recognize hand written digit recognition. This model is giving 99.54% on test set